Off-Label Use of Thrombopoietin Receptor Agonists: Case Series and Review of the Literature - Capecchi, Marco; Serpenti, Fabio; Giannotta, Juri; Pettine, Loredana; Reda, Gianluigi; Martinelli, Ida; Artoni, Andrea; Barcellini, Wilma; Fattizzo, Bruno (Frontiers in Oncology, 2021)
Since their license in 2008, studies on thrombopoietin receptor agonists (TPO-RA) are proceeding at a fast pace. Their favorable efficacy and safety profile makes them good candidates for the management of thrombocytopenia in different settings, even beyond their current indications. In the last ten years, we faced patients with refractory thrombocytopenia that required treatment with off-label TPO-RA, despite the paucity of data in the literature and the possible risks, particularly that of thrombosis. We hereby report our ten years real-life single-center experience of TPO-RA used off-label. Fourteen patients were divided into three groups according to the etiology of thrombocytopenia: myelodysplastic syndromes, post-transplantation, and lymphoproliferative diseases. Clinical features and results are reported within each group. Overall, TPO-RA proved effective in all these conditions achieving responses also in heavily pretreated patients. Overall response rate (ORR) was 100% in patients with thrombocytopenia after transplantation and in those with lymphoproliferative diseases and 75% in patients with myelodysplastic syndromes. Median duration of therapy was 285 days (range 93-1513 days). Four patients (29%) discontinued treatment, because of lack of response (n=2) or a sustained response (n=2). No grade 3-4 adverse events occurred, particularly no thrombosis. In our real-life experience, TPO-RA were effective and safe and proved of value in the challenging management of patients with refractory thrombocytopenia associated with different conditions.